Динамічний стретчинг у процесі фізичного виховання волейболістів - Афанасьєва, Олена Миколаївна; Натарова, Вікторія Вікторівна; Недбайло, Ірина Анатоліївна (Видавничий дім "Гельветика", 2022)
Ефективними засобами здійснення фізичної активності для студентів вищих навчальних закладів є ігрові види спорту, які накладають конкретні вимоги щодо розвитку певних фізичних якостей. Дослідницька робота присвячена перевірці ефективності використання динамічного стретчингу для покращення показників гнучкості у студентів, які займаються волейболом на 2 – 3 курсах навчання. Збір даних здійснювався на заняттях з фізичного виховання (секція волейбол) в основній групі Національного технічного університету «Харківський політехнічний інститут». Результати дослідження виявили ефективність та безпечність запропонованого методу розвитку гнучкості та рухливості суглобів для студентів, які займаються волейболом. Динамічний стретчинг можна рекомендувати для впровадження у робочу програму з волейболу, а також для самостійних занять студентів.

Effective ways of doing physical activity for students of higher educational institutions are playing sports, which have specific requirements for the development of certain physical qualities. One of these is dynamic stretching - a set of exercises that allows you to develop muscles and joints in the full range. This research is about testing the effectiveness of the use of dynamic stretching to improve flexibility for students who play volleyball in 2 – 3 courses. Data collection was carried out in physical education classes (volleyball section) in the main group of the National Technical University "Kharkiv Polytechnic Institute". The results of the study revealed that the proposed method of developing flexibility and mobility of joints for students who play volleyball is effective and safe. It was found that dynamic stretching avoids muscle strain during sports, makes the muscles stronger and the body flexible. Since with dynamic muscle stretching, the intensity and speed of movement increases gradually, the risk of injury is minimal. Also, stretching benefits were found to reduce muscle tension, improve blood circulation, correct posture, and increase endurance. After the start of the dynamic stretching, the students experienced improvements in their overall training results. The dynamic stretching can be recommended for implementation in the work program in volleyball, as well as for independent workouts of students. Dynamic stretching is recommended to be completed as a warm-up before exercising. Also, dynamics can be performed as a full-fledged workout with a previous warm-up, since many dynamic exercises also carry a power load on the body and muscles, strengthening them.
Dynamic stretching in the process of physical education of volleyball players
Keywords: динамічний стретчинг; студенти; волейбол; фізичне виховання; гнучкість; dynamic stretching; students; volleyball; physical education; flexibility